2014
DOI: 10.1038/ki.2013.501
|View full text |Cite
|
Sign up to set email alerts
|

Renal cyst growth is the main determinant for hypertension and concentrating deficit in Pkd1 -deficient mice

Abstract: We have bred a Pkd1 floxed allele with a nestin-Cre expressing line to generate cystic mice with preserved GFR to address the pathogenesis of complex ADPKD phenotypes. Hypertension affects about 60% of these patients before loss of renal function, leading to significant morbimortality. Cystic mice were hypertensive at 5 and 13 weeks of age, a phenotype not seen in non-cystic controls and Pkd1-haploinsufficient animals, which do not develop renal cysts. Fractional sodium excretion was reduced in cystic mice at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 45 publications
2
35
2
14
Order By: Relevance
“…HTG+ animals were shown not to have increased mean arterial pressure (MAP) at 13 wk in the 129Sv background (14) and our current study has confirmed this finding in the C57BL/6 background (Table S4). On the other hand, we have previously shown that CYG+ mice presented elevated MAP at 5 and 13 wk in the C57BL/6 background (14), while a non-significant higher numerical value was observed at 24 wk (Table S4).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…HTG+ animals were shown not to have increased mean arterial pressure (MAP) at 13 wk in the 129Sv background (14) and our current study has confirmed this finding in the C57BL/6 background (Table S4). On the other hand, we have previously shown that CYG+ mice presented elevated MAP at 5 and 13 wk in the C57BL/6 background (14), while a non-significant higher numerical value was observed at 24 wk (Table S4).…”
Section: Resultssupporting
confidence: 78%
“…Homozygous mice for a Pkd1- floxed allele, in turn, with a mosaic pattern of gene inactivation driven by a Nestin-Cre transgene and excision of exons 2–4 ( Pkd1 cond/cond : Nestin cre ; CYG+) (14, 17), developed a milder renal phenotype in our animal-care facility than in another center (14, 19). The CYG+ mice develop cystic kidneys and increased mean arterial pressure (MAP) (14), reproducing the ADPKD phenotype, however do not have a systemic Pkd1 -haploinsufficiency background. Noncystic animals ( Pkd1 cond/cond ; NC) were their controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause for this early hypertension has been related to cyst compression of normal renal structures and activation of the intrarenal renin-angiotensin system (33). However, a recent study (9) found that hypertension was present in a mouse model of Pkd1 deficiency when only minimal renal cysts were present. Notably, while renal ET-1 production is increased in cystic kidney disease after significant renal damage has occurred, there is no information on renal or CD ET-1 production in kidneys without functional polycystin-2 but before cysts form.…”
Section: F549mentioning
confidence: 96%
“…Nesse contexto, destacam-se os efeitos da hipertensão arterial sistêmica (HAS), presente em cerca de 60% dos pacientes com DRPAD antes mesmo de prejuízos na função renal serem detectados 13,14 e 10 anos antes que na população geral 15 . A gênese da HAS ainda não está completamente elucidada na DRPAD, porém a ativação do sistema renina-angiotensina-aldosterona (SRAA) em resposta à compressão vascular decorrente da distensão dos cistos parece cumprir um papel central na determinação desse fenótipo 16 . O desenvolvimento de hipertrofia ventricular esquerda e de miocardiopatia dilatada idiopática também impactam no prognóstico da doença 17,18 .…”
Section: Epidemiologia E Manifestações Clínicasunclassified